Kinerja Modal Intelektual Industri Perbankan Di Indonesia: Apakah Corporate Governance Berpengaruh? - Isna Putri Rahmawati; Andi Asrihapsari; Vidia Ayu Satyanovi; Nasyi'ah Hasanah Purnomowati (JRAK: Journal of Accounting Research and Computerized Accounting, 2023)
The purpose of this study is to provide empirical evidence regarding the effect of corporate governance (CG) practices on the performance of a company's intellectual capital. CG practices studied are the proportion of independent commissioners, the number of commissioners, and the number of audit committees. The dependent variable in this study is the performance of intellectual capital as measured by Value Added Intellectual Capital (VAIC). The sample for this research is banking companies listed on the Indonesia Stock Exchange in 2015-2021 with a total of 248 observations. The results of this study are independent commissioners can improve the performance of intellectual capital. However, the board of commissioners and the audit committee do not affect intellectual capital performance.